Uji Efektivitas Pupuk Majemuk NPK yang Ditambah Asam Humat terhadap Pertumbuhan dan Produksi Tanaman Padi - RUSTIATI, TITA (Agrotrop : Journal on Agriculture Science; Vol 3 No 2 (2013), 2015)
Study on The Effectivityof NPK Compound FertilizerAdded withHumic Acid for Growthand Pruductionof Rice.It is important to improve the efficiency of fertilizers especially nitrogen (N)for lowland rice cultivation, since the efficiencyof broadcasted N was ony in the range of 30–40%,while P fertilizer 20–30% and K fertilizer 30–40%. Humic products have been used for years inproduction agriculture with varying results to improve plant growth and yield, as well as increasingfertilizer efficiency.Field experiment has been conducted at Experimental Farm of Rice Research InstituteinSukamandi to evaluate the effectivity of humic acid addition to NPK compound fertilizer on lowlandrice. Five doses (200, 250, 300, 350, and 400 kg/ha) of compound fertilizers NPK-1 and NPK-2(NPK+humic acid), together with control and local recomended fertilizer were tested in this experiment.Twelve treatments with 4 replications were arranged in Completely Randomized Block Design.Resultsof experiment showed that in general compound NPK fertilizer did not give better result if humic acidwas added; the effectivity of NPK compound fertilizer was not affected by the addition of humic acid.Humic acid tended to increase N use efficiency at higher level of fertilizer. It was suggested that withhigher level of humic acid theeffect would be more significant.
Keywords: compound fertilizer; humic acid; fertilizer efficiency